2020
DOI: 10.1007/s12265-020-10001-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immunomodulation in Vein Graft Remodeling and Failure

Abstract: Obstructive arterial disease is a major cause of morbidity and mortality in the developed world. Venous bypass graft surgery is one of the most frequently used revascularization strategies despite its considerable short and long time failure rate. Due to vessel wall remodeling, inflammation, intimal hyperplasia, and accelerated atherosclerosis, vein grafts may (ultimately) fail to revascularize tissues downstream to occlusive atherosclerotic lesions. In the past decades, little has changed in the prevention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 101 publications
(132 reference statements)
1
14
0
Order By: Relevance
“…Histopathological studies and experimental vein graft models have shown that the inflammatory components of the innate immune system are present in all stages of vein graft adaptation (21). Crucial for a long-term good vein graft patency is the proper amount of vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological studies and experimental vein graft models have shown that the inflammatory components of the innate immune system are present in all stages of vein graft adaptation (21). Crucial for a long-term good vein graft patency is the proper amount of vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…A certain degree of inflammation is beneficial in the process of remodeling (22). Inflammatory cytokines and growth factors excreted by leukocytes invading the vessel wall contribute to the reendothelialization of the, during the surgery, damaged endothelium and activate smooth muscle cell migration and activation (1,21,22). This inflammatory trigger needs to dampen after the initial period to drive the remodeling process toward the positive outward remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…We present the results of early reperfusion, suggesting that overactivity of the inflammatory system following off-pump procedures can predispose patients for graft endothelium injury as proinflammatory cytokines are released. The role of immunomodulation in vein graft failure in humans was reviewed by Baganha et al [ 64 ]. Immune cells in long-term intimal hyperplasia and accelerated atherosclerosis were presented on experimental and clinical basis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that the immune system plays a critical part in tissue maintenance and repair beyond its traditional role of distinguishing self from non-self and eradicating pathogens (31). In recent years, the immune system has been recognized as an important contributor to a number of cardiovascular diseases, including hypertension, atherosclerosis, and the vasculitides (15,16,(18)(19)(20)32). While the intact vascular endothelium is not immunologically reactive, if the blood vessels become damaged, further vascular injury may occur through a variety of innate and adaptive immune mechanisms (33,34).…”
Section: Discussionmentioning
confidence: 99%